Influence of atmospheric vertical wind and turbulence on noctilucent clouds - Vellalassery, Ashique; Baumgarten, Gerd; Grygalashvyly, Mykhaylo; Lübken, Franz-Josef; Udayakumar, Gokul (Frontiers in Astronomy and Space Sciences, 2026)
Noctilucent clouds (NLCs), also called Polar Mesospheric Clouds (PMC), are high-altitude ice clouds in the summer mesopause region, mainly at polar latitudes. Their formation is sensitive to local atmospheric conditions, such as water vapor and temperature, as well as dynamics. This study investigates the impact of vertical transport, specifically turbulence and vertical winds, on NLC microphysics and background water vapor distribution using the three-dimensional transport model MIMAS (Mesospheric Ice Microphysics And tranSport model). We conducted numerical simulations of NLCs considering heterogeneous nucleation only with varying turbulence and vertical wind conditions, including cases with a 2× increase and a 0.5× reduction in the values of both parameters. Our results show that increased turbulence broadens the vertical distribution of ice particles, forming smaller ice particles that result in less bright clouds and a reduced freeze-drying effect, with a ∼7% decrease in peak mean particle radius and a ∼30% drop in peak mean brightness. In contrast, increased vertical winds enhance the upward transport of water vapor and reduce the net downward sedimentation speed of ice particles, thereby increasing water vapor concentration at mesopause altitudes and allowing particles to remain longer in supersaturated regions. This promotes the growth of larger ice particles and results in a ∼26% increase in peak mean particle radius and a ∼260% increase in peak mean brightness. These results highlight the different roles of turbulence and vertical winds in shaping NLC properties and background water vapor distribution, with implications for improving the modeling of NLCs and improving our understanding of how NLCs respond to long-term changes in upper atmospheric conditions.